2021
DOI: 10.1038/s41467-021-24011-0
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic basal complex modulates mammalian sperm movement

Abstract: Reproductive success depends on efficient sperm movement driven by axonemal dynein-mediated microtubule sliding. Models predict sliding at the base of the tail – the centriole – but such sliding has never been observed. Centrioles are ancient organelles with a conserved architecture; their rigidity is thought to restrict microtubule sliding. Here, we show that, in mammalian sperm, the atypical distal centriole (DC) and its surrounding atypical pericentriolar matrix form a dynamic basal complex (DBC) that facil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 65 publications
3
56
0
Order By: Relevance
“…2A ). These data, in agreement with previous reports ( Fishman et al , 2018 ; Khanal et al , 2021 ), suggest that the human sperm basal body might be associated with centrosomal proteins. Altogether we conclude that the human sperm basal body includes two centrioles that show some basic features of conventional centrosomes, suggesting that it might not undergo a full process of centrosome reduction and establishing the foundation to perform a large scale approach to identify the human sperm PCM ( Manandhar et al , 2000 ; Manandhar and Schatten, 2000 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…2A ). These data, in agreement with previous reports ( Fishman et al , 2018 ; Khanal et al , 2021 ), suggest that the human sperm basal body might be associated with centrosomal proteins. Altogether we conclude that the human sperm basal body includes two centrioles that show some basic features of conventional centrosomes, suggesting that it might not undergo a full process of centrosome reduction and establishing the foundation to perform a large scale approach to identify the human sperm PCM ( Manandhar et al , 2000 ; Manandhar and Schatten, 2000 ).…”
Section: Resultssupporting
confidence: 93%
“…The localization of a subset of human sperm centrosomal proteins has been recently described using IF ( Fishman et al , 2018 ; Khanal et al , 2021 ) and our proteomic analysis further identified 7 out of 20 proteins that Fishman et al (2018) already described. Interestingly, we identified three centrosomal proteins that could not be detected by IF analysis (γ-tubulin chain 1, pericentrin and PCM 1), either because of technical limitations, such as accessibility in fixed samples, or their very low abundance, opening the possibility that many other centrosomal proteins may also be present in the basal body of the mature sperm.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations